Resepsi Paham Konservatisme Komunitas Pemuda Hijrah pada Perguruan Tinggi Islam di Kota Kendari - Ahmad, Ahmad; Iqbal, Muhammad (Institut Agama Islam Negeri Kendari, 2023)
This study aims to explore the relationship between fiqh learning and the understanding of conservatism that develops in Islamic higher education (PTI) by exploring the fiqh learning pattern of young hijrah students in Kendari city. Their fiqh learning patterns were analyzed using the Living Fiqh approach, so that they could form factors that indicated a relationship between the two variables. Sources of data in this study are divided into two types, namely primary data and secondary data. The primary data consisted of fiqh materials for youths who moved from IAIN Kendari and UMK. As for the secondary data in the form of classic and modern fiqh books scattered in the youth movement phenomenon community, literature data in the form of the migration of the younger generation which is in line with the research and responses of fiqh experts were collected through Focus Group Discussions. The results of this study indicate that the sources of understanding of the conservatism of the young emigrated are more dominant that they get outside the campus, including seasonal recitations at mosques and social media. Based on these findings, the development of fiqh learning in PTI must be able to adapt to digital media. The implications of this research are presented at the end of the research.